Scedosporium prolificans Septic Arthritis and Osteomyelitis of the Hip Joints in an Immunocompetent Patient: A Case Report and Literature Review. (10th January 2017) - Daniele, Luca; Le, Michael; Parr, Adam Franklin; Brown, Lochlin Mark
Abstract : Scedosporium prolificans, also known as Scedosporium inflatum, is a fungus widespread in soil, sewage, and manure. This species is highly virulent and is an emerging opportunistic pathogen found in penetrating injuries in immunocompromised patients. Here we report on an immunocompetent patient with bilateral hip S. prolificans -associated osteomyelitis and septic arthritis caused by intentional penetrating trauma. The condition was refractory to initial antimicrobial suppression and surgical irrigation and debridement. Successful outcome was achieved after incorporating a bilateral two-stage total-hip-arthroplasty with Voriconazole-loaded cement and spacer.